A study of intent of suicide in people with major depression - Shukla, Devashish; Jilani, Abdul Qadir; Jaisawal, Priyanka; Mail, Anil Nischal; Singh, Jai Veer; Kallivayalil, Roy Abraham (Indian Journal of Community Health, 2016)
Background: Depression is most important underlying diagnosis among the cases of suicide. There is dearth of information regarding suicidal intent among people of depression and its relationship with hopelessness among Indians. Aims & Objective: To describe the intent of suicide in people with depression among the north Indian population. Material & Methods: This was a cross-sectional study at department of psychiatry, King George's Medical University, Lucknow. Subjects between age group of 18-60 years with major depressive disorder as per DSM-IV TR criteria were screened and included in the study. Each subject was assessed using Hamilton Depression Rating Scale (HRS), Beck’s Hopelessness Scale (BHS) and Suicide Intent Questionnaire (SIQ). Results: Suicidal intent was observed among 68.1% (n=49) of sample (n=72). There was no significant (p>0.05) association of suicidal intent with socio-demographic factors except domicile status. Suicidal intent was common among people with moderate to severe depression and those with hopelessness. The hopelessness was present among 70.8% of subjects. Conclusion: Suicidal intent is common among people with major depression. The authors emphasize the need of exploration of suicidal intent in people with depression.